Coping With Negative Stereotypes Toward Older Workers: Organizational and Work-Related Outcomes - Chiesa, Rita; Zaniboni, Sara; Guglielmi, Dina; Vignoli, Michela (Frontiers in Psychology, 2019)
The current study aims to test a moderated-mediation model in which occupational self-efficacy determines the indirect effect of negative stereotypes about older workers in the organization both on psychological engagement in the work domain and on attitudes toward development opportunities through identification with the company. The survey involved 1,501 Italian subjects aged over 50 who were employed by a major large-scale retailer. Consistently with the Social Identity Theory and the Social Exchange Theory, results showed that the perception of negative stereotypes about older workers in the organization is associated with low identification with the company and, subsequently, with poor psychological engagement in the work domain and with attitudes indicating very little interest in development opportunities. In addition, this association was found to be stronger in older workers with higher and medium levels of occupational self-efficacy. These findings suggest that organizations should discourage the dissemination of negative stereotypes about older workers in the workplace because they may lead to older workers’ disengagement from the work domain and their loss of interest in development opportunities.